Analisis Penggunaan Jargon Bahasa Komunitas Game Online PUBG Mobile di Kota Samarinda - Iskandar, Fitriyanti; Agustian, Jaka Farih; Putri, Nina Queena Hadi (Universitas Mulawarman, 2021)
Groups in society use jargon to communicate using their own more specific language, therefore they can foster a sense of ownership or loyalty to a particular group. Jargon is usually used so that gamers know the meaning of a certain group word in a group of people or to show identity. them, for example in playing the PUBG Mobile Game, researchers feel the need for deepening of the forms and benefits of terms that are often not understood by community groups in general. Jargon shows how many options are available. The place you live in, the age you have, the social level you occupy can show the diversity of language variations. This study aims to (1) describe the form of jargon used in the PUBG Mobile online game community in the city of Samarinda. (2) Describe the meaning of jargon used in the PUBG Mobile online game community in the city of Samarinda. (3) Describe the function of the jargon used in the PUBG Mobile online game community in the city of Samarinda. The research method used is a qualitative descriptive research method and the data that becomes the object is the language jargon used by the PUBG mobile online game community. The data collection techniques were observation, note taking, recording, and direct fishing. Based on the results of data analysis, the forms of jargon found in this research are the basic Indonesian word form, reduplication form, abbreviation form, acronym form and adaptation form. The meaning found in this study is in the form of lexical meaning and contextual meaning. The function of the PUBG Mobile game community jargon is to facilitate communication between PUBG Mobile players.